Retailing in India-what’s Up? - Sudhakar, G. P. (Indian Journal of Marketing, 2005)
"Conventional retailers, especially those that are mid-sized, will be squeezed from all sides; from larger players with better economies of scale, from smaller players with more focused selection or a greater emphasis on convenience; from electronic retailers that have few physical assets but are rich in information, and from entertainment and education oriented players that offer a more vibrant consumer experience." Jagdish Sheth with Rajendra.S.Sisodia - "Changing Face of Retailing" Financial Times - series on Managing Marketing - Oct 19, 1998. Using the article by Jagdish Sheth with Rajendra.S.Sisodia titled "Changing Face of Retailing" published in 1998 as a reference point and generously borrowing the dimensions to examine retailing trends, one can notice the following in Indian retailing.